1980
DOI: 10.1111/j.1432-1033.1980.tb04396.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Ribosylthymine in Transfer RNA

Abstract: In some eucaryotes tRNA species occur containing exclusively uridine or ribosylthymine at position 54. In other eucaryotic tRNA species varying ratios of uridine to ribosylthymine have been found. To elucidate whether variation in the degree of U54 methylation in eucaryotic tRNA plays a functional role in protein synthesis, polysomal and overal cellular tRNAs in the lower eucaryote Dictyostelium discoideum were characterized during vegetative growth and the early developmental preaggregation stage.The nucleosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Similarly the presence of the modified base Q in the anticodon of several mammalian tRNAs is related to the cell differentiation (Dingermann et al 1981) and is also found to be different in normal and cancer cells (Okada et al 1978, Shindo-Okada et al 1981. Similar experiments with intact tRNA species, modified on the residue-54 to different extents, provide similar results (Dingermann et al 1980. Sprinzl and Gauss (1982).…”
Section: Trna Modificationmentioning
confidence: 78%
“…Similarly the presence of the modified base Q in the anticodon of several mammalian tRNAs is related to the cell differentiation (Dingermann et al 1981) and is also found to be different in normal and cancer cells (Okada et al 1978, Shindo-Okada et al 1981. Similar experiments with intact tRNA species, modified on the residue-54 to different extents, provide similar results (Dingermann et al 1980. Sprinzl and Gauss (1982).…”
Section: Trna Modificationmentioning
confidence: 78%
“…Modified bases located adjacent to the anticodon were shown to enhance the codon-anticodon interaction (22). Moreover, it has been shown that tRNAs containing ribosyithymidine at position 54 predominate on polysomes (3) and are more efficient for in vitro protein synthesis than their U54-containing counterparts (26). However, this possible selection cannot account alone for the observed differences in the tRNA distribution between whole-cell and polysomal preparations, as some amino acid-specific tRNA groups were found in quite different proportions in both preparations.…”
Section: Resultsmentioning
confidence: 99%
“…The nucleic acids were precipitated from the aqueous phase with 2.5vol. of ethanol, dissolved in electrophoresis buffer and applied to electrophoresis on a 10% polyacrylamide gel (Dingermann et al, 1980).…”
Section: Organism and Culture Conditionsmentioning
confidence: 99%